Divorce outside the Court According to Fiqh - Wani Maulida Alsa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Divorce is the act of the husband with his pledge which aims to eliminate and release the marriage bond by using certain words. The fiqh perspective explains that divorce talak is an utterance with clear words to indicate divorce. However, if you look at the legality of divorce according to positive law, divorce according to the Compilation of Islamic Law in Indonesia which is regulated in chapter XVI regarding the Dissolution of Marriage in Article 117 which reads that divorce is the husband's pledge before a Religious Court session which is one of the reasons for the breakup of a marriage according to the procedure certain way. In practice, in Islamic society in Indonesia, for the sake of valid divorce for a husband who wants to divorce his wife, then a valid divorce can only be carried out by the husband in front of the Religious Court. So when viewed from a legal context, as a result of divorce cases that are not submitted to the Religious Courts for Muslim communities who want to divorce, then it is still considered a husband and wife marriage bond. The status of talaq outside the court is invalid, because the divorce is not carried out before a court session and if it is seen that there are more harms than benefits. Then the legal consequences that arise after the divorce is more clearly regulated, so that the obligations and rights that arise after the divorce are more secure and no one feels intervened between the two parties who want to divorce.